Impulse Conductometry as the Express-Test to Estimate the State of 2-Cell Murine Embryos - Strikha, Oksana A. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):174.